Advantages of Additive Technologies Usage in Design of Cooling Channels - Raz, Karel (Manufacturing Technology Journal, 2019)
Main aim of this paper is to analyze the thermal behavior of different cooling channels and to describe advantages of manufacturing of a mold with these channels using a 3D printer instead of drilling machines. This work was primarily done by the usage of virtual simulation. Validation of thermal simulations was performed by usage of simple analytical solution. A simple model of molded brick was designed to analyze the cooling time and the temperature distribution in the mold when changing the cross section of the cooling channels. Three types of different rectangular cross-sections and one circular were chosen. All of them have the same area. The cooling channel with circular cross section was positioned closer to the part in next design and influence of this change was analyzed. Last tested configuration is conformal cooling channel with a channel path twice longer. It is obvious, that most suitable configuration of cooling channels is combination of conformal design with rectangular shape as close as possible to plastic part.
Keywords: Injection Molding; Cooling; Additive Technologies